Primary omental infarction: a rare cause of acute abdomen - Pawar, Neeraj; Kishore, Anand (International Surgery Journal, 2020)
Primary omental infarction (POI) is a rare cause of acute abdomen. It frequently mimics other causes of acute abdomen. It is being diagnosed more frequently with the advancement of radiology. Here we report a case of a 35 years old man admitted in emergency with pain right side abdomen since past 2 days. On physical examination patient was febrile with tenderness and guarding over right side of abdomen, TLC (total leucocyte count) - 13.2×109/l, mild rise in bilirubin with rest blood investigations being normal. CT (computed tomography) abdomen was s/o omental infarction. On diagnostic laparoscopy gangrenous omentum with torsion over a vascular pedicle was noted, omentectomy was performed laparoscopically. In conclusion omental infarction should be kept as a differential diagnosis in acute abdomen especially right-side abdominal pathologies. It can be managed conservatively but if signs of sepsis are there it is wise to perform a diagnostic laparoscopy.